The use and ethical implications of artificial intelligence, collaboration, and participation in local Ibero-American newsrooms - García de Torres, Elvira; Ramos, Giovanni; Yezers’ka, Lyudmyla; Gonzales, Mayra; Higuera, Liza; Herrera, Claudia (Frontiers in Communication, 2025)
This study examined the use and ethical implications of Artificial Intelligence (AI), collaboration, and participation in 12 local Ibero-American news outlets across Brazil, Colombia, Ecuador, Spain, Mexico, Peru, and Portugal. Based on data from 138 questionnaires, the findings highlighted limited knowledge and technical expertise, along with serious ethical concerns. While journalists expressed positive attitudes toward collaboration with other newsrooms and audience participation, their practical implementation remained low. Regarding AI, there was broad consensus against its use in content production, even though adoption levels mirrored those of collaboration and participation. Ethical concerns surrounding AI were widespread, whereas collaboration was more frequently associated with enhancing journalistic quality. The analysis of country-level consistency revealed significant variations in innovation adoption. The findings emphasized the urgency of targeted training programs and specific ethical guidelines, as well as the need to advance research on hybridization in journalism to help local news media navigate the evolving media landscape.